Developing Underwater Video Media in Learning Basic Swimming Techniques - I Gede Suwiwa; I Ketut Budaya Astra; Septyan Pemardo Pasaribu (STAI Hubbulwathan Duri, 2022)
The purpose of this research was to develop instructional video media for basic swimming techniques using the ADDIE model. The development aims to (1) identify the feasibility level of the media through the responses of experts (2) the effectiveness of the media developed. The data were collected by using questionnaire and a field testing. The result of experts’ judges showed that content experts 64% (enough), learning media experts 76% (good) and learning design experts 78% (good). The results of the study were based on the responses of individual students 83% (good), small group 98.67% (very good), and large group 89.42% (very good). The students’ swimming performance was assessed based on distance, hand, feet, breathing, and coordination movements. The result of field testing showed that students’ swimming performance after the implementation of underwater video media was better than before the implementation (Sig.2-tailed=.001). Thus, the underwater video media is suitable to be used in teaching basic swimming technique based on the result of expert and field testing. This development research is expected to help in making, using and creating creative learning and to solve problems, especially in the material of swimming theory and practice.